Impact of the increased active surface of the platinum catalyst on the total ammonia recovery coefficient - Trumić B.; Stanković D.; Trujić V. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In order to increase the active surface of platinum catalysts for ammonia oxidation and on the basis of theoretic considerations and tests in industrial environment, we have finally decided on their specific design. Efficiency on the newly designed catalyst was checked in industrial circumstances. A comparative analysis of the total ammonia recovery coefficient between the mentioned new catalysts and previously applied platinum catalysts was carried out. All advantages of catalysts with increased active surfaces were confirmed and a new method of their manufacturing process was selected.